Annihilation: conquest (2008), book 2 ebook Conquest book 2 - special. - Abnett, Dan (Annihilation: Conquest (2008),, 2013)
Collects Annihilation: Conquest #1-6, Nova #4-7 & Annihilation: Conquest - Wraith #1-4. In the wake of the Phalanx's sneak attack on the Kree Empire, heroes band together to liberate a galaxy in peril. What are the Phalanx really after? Grab your weapon and join the fight for freedom with Wraith, Nova, Quasar, Star-Lord, and more! Author: Javier Grillo-Marxuach, Dan Abnett, Andy Lanning. Illustrator: Kyle Hotz, Sean Chen. © 2019 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com